Ecological Differences in Weight, Length, and Weight for Length of Mexican American Children in the WIC Program - Reifsnider, Elizabeth (J Spec Pediatr Nurs, 2008)
PURPOSE: Examine factors common in the environments of children who obtain services from a WIC program to determine if differences in ecological/environmental factors can be found in the children who differ in weight, length, and weight for length. DESIGN AND METHODS: Cross-sectional study of 300 children, 100 each who were stunted, normal weight for length, or overweight. Instruments used were NCATS, ARSMA II, 24-hr diet recall, and Baecke Activity Questionnaire. RESULTS: Significant differences were present in children’s diet, parents’ BMI, parents’ generation in United States, parents’ activity levels, and maternal–child relationship. PRACTICE IMPLICATIONS: Encourage parents to adopt family approaches to encourage normal body size in children.